Effect of dielectric constant on the plasma characteristics of a dielectric barrier discharge reactor - Noushin Dadashzadeh (Journal of Optoelectronical Nanostructures)
This research investigates the effect of dielectric constant variations of insulating materials on the plasma characteristics of a dielectric barrier discharge reactor at atmospheric pressure. Numerical simulations demonstrate that changes in the dielectric constant can significantly influence the spatial distribution of the plasma, electric field strength, and other key discharge parameters. The results of this study are crucial for the optimal design of DBD reactors in a wide range of applications, including plasma processing, ozone generation, and water treatment.